Correlation and path analysis of body weight and biometric traits of Nguni cattle breed (Journal of Advanced Veterinary and Animal Research, 2020)
Objective: This work was conducted to examine the association between body weight (BW) and biometric traits viz. head width (HW), head length (HL), ear length (EL), body length (BL), rump height (RH), withers height (WH), sternum height (SH), rump width (RW), and heart girth (HG) and to determine the direct and indirect effects of biometric traits on BW.Materials and Methods: Sixty female and twenty male Nguni cattle between the ages of one to four years were used. Pearson correlation and path analysis were used for data analysis.Results: Correlation results recognized that BW had a positive highly significant correlation with RW (r = 0.70**), RH (r = 0.90**), HG (r = 0.90**), SH (r = 0.90**), and WH (r = 0.93**) in male, whereas SH (r = 0.34**), WH (r = 0.55**), RH (r = 0.70**), and HG (r = 0.76**) had a positive highly significant correlation with BW of female Nguni cattle. Path analysis showed that RW (13.35) had the highest direct effect, whereas SH had an indirect effect on BW of male Nguni cattle. In female Nguni cattle, RH (4.87) had the highest direct effect, whereas HL had an indirect effect on BW.Conclusion: Association findings suggest that improvement of RW, RH, HG, SH, HG, and WH might result in the increase in BW of Nguni cattle. Path analysis results suggest that RW and RH might be used as a selection criterion during breeding to increase BW of Nguni cattle. The results of the current study might be used by cattle farmers to estimate BW using biometric traits.J. Adv. Vet. Anim. Res., 7(1): 148-155, March 2020